Effect of Adoption of Fourth Industrial Revolution Technologies on Health and Safety Practices of Workers in Construction Projects in Abuja - Olabanji M. KADI; Abdullateef A. SHITTU, (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
This study assessed the effectiveness of 4IR technologies for effective H&S in construction projects in Abuja with a view to enhancing the safety performance of employees at construction workplace. The study adopted the quantitative research approach using the survey research design. Data were collected from 127 professionals of construction firms operating in Abuja and listed in the Abuja Business Directory online, at a response rate of 96.85%. Analysis of data was carried out with the use of both descriptive statistics such as frequency count, percentage and Mean Item Score (MIS) and inferential analytical techniques such as Spearman Rank Correlation analysis. The results of the analysis revealed that the severe barrier to the adoption of 4IR technologies for effective H&S practices in construction projects is “Insufficient electricity” (MIS = 4.55). The most significant driver for the adoption of 4IR technologies for effective H&S practices in construction projects is “Getting ready to adopt Digital drivers” (MIS = 4.16). It was also revealed that there exists a strong, positive and significant relationship between the adoption of 4IR technologies for H&S practices of workers and the drivers for the adoption of 4IR technologies for effective H&S practices in construction projects (r = 0.611; p = 0.000). The study concludes that the effect of adoption of 4IR technologies on the H&S practices of workers in construction projects is significant and can enhance the safety performance of employees at construction workplace. The study recommends that in order for construction firms to enhance the adoption of 4IR technologies and to sustain it, there is a need to develop a mechanism which will be made up of both proactive and reactive measures based on the drivers for the adoption of 4IR technologies for effective H&S practices in construction projects identified in this study.